Clinical approach to nadivrana W.S.R to pilonidal sinus - Amareshappa; Manoj Kumar; Shailaja S V (International Journal of Pharmacy and Analytical Research, 2022)
The term Nadi vrana implies a tube-like structure and Nadi vrana means sinus. Nadi vrana is a secondary condition of improper drainage of abscess, negligence of foreign body in wound, tuberculosis. Pakvashopha upeksha, Anuchita paatanakarma, Mithya aahar&vihara, Shalya are the main cause for nadi vrana. Sushruta classified nadivrana into vataja, pittaja, kaphaja, sannipataja, dwandwaja, agantuja whereas vagbhata classified the same except dwandwaja. Sadhyasadhyata asTridosha is Asadhya & vataja, pittaja, kaphaja, dwandaja and shalyaja are saadhya. Varti prayoga, ksharasutra & shastra karma are the treatment of choice in nadivrana. Nadivrana can be compaired to sinus and shalyaja / agantuja nadivrana as pilonidal sinus. Sinus is a blind track leading from surface down into the tissue and lined by granulation tissue. It is mostly formed secondary to abscess and most of the time results into fistula. Treatment includes proper Antibiotics, adequate rest, adequate excision, adequate drainage & treat the secondary causes. Pilonidal sinus is a common disease of the natal cleft in the sacrococcygeal region with weak hair accumulation occurring in the hair follicles, which can be chronic and undergo acute exacerbation. The patient presents with the complaints, which are characteristics of inflammation-a painful swelling, redness, local temperature raised or with a sinus discharge. There are 2 types as primary- opens in midline, secondary opens lateral to midline. The Causes for reoccurrence are improper removal of track, entry of new tuft of hairs, breakage of scar, irregular shaving of hair, improper hygiene. Regular shaving of the hair in natal area, proper perianal hygiene, proper drainage of the pus, avoid the causative factors are the preventive measures for pilonidal sinus. Treatment includes surgical management, it is of 2 types. Close surgery includes, excision with primary closure and flap closure. Open surgery includes conventional wide excision and laser pilonidoplasty